2D Materials for Gas Sensing Applications: A Review on Graphene Oxide, MoS2, WS2 and Phosphorene - Maurizio Donarelli (Sensors, 2018)
After the synthesis of graphene, in the first year of this century, a wide research field on two-dimensional materials opens. 2D materials are characterized by an intrinsic high surface to volume ratio, due to their heights of few atoms, and, differently from graphene, which is a semimetal with zero or near zero bandgap, they usually have a semiconductive nature. These two characteristics make them promising candidate for a new generation of gas sensing devices. Graphene oxide, being an intermediate product of graphene fabrication, has been the first graphene-like material studied and used to detect target gases, followed by MoS2, in the first years of 2010s. Along with MoS2, which is now experiencing a new birth, after its use as a lubricant, other sulfides and selenides (like WS2, WSe2, MoSe2, etc.) have been used for the fabrication of nanoelectronic devices and for gas sensing applications. All these materials show a bandgap, tunable with the number of layers. On the other hand, 2D materials constituted by one atomic species have been synthetized, like phosphorene (one layer of black phosphorous), germanene (one atom thick layer of germanium) and silicone (one atom thick layer of silicon). In this paper, a comprehensive review of 2D materials-based gas sensor is reported, mainly focused on the recent developments of graphene oxide, exfoliated MoS2 and WS2 and phosphorene, for gas detection applications. We will report on their use as sensitive materials for conductometric, capacitive and optical gas sensors, the state of the art and future perspectives.